Analisis Tingkat Erosi Menggunakan Metode USLE di Kapanewon Panggang Kabupaten Gunungkidul Daerah Istimewa Yogyakarta - Atmojo, Surya; Suwadji, Siman (Jurnal Wana Tropika, 2024)
One of the causes of critical land is erosion; the greater the intensity of erosion, the more critical the land becomes. The distribution of erosion predictions is influenced by variables such as rainfall erosivity, soil erodibility, slope length and steepness, ground cover vegetation, land use, and land conservation. One of the critical lands is located in Kapanewon Panggang, Gunungkidul Regency, Special Region of Yogyakarta, covering an area of 9130.01 hectares, which consists of six villages: Giriharjo, Girisuko, Giriwungu, Girimulyo, Girikarto, and Girisekar. The purpose of this study is to determine the erosion rate in Kapanewon Panggang, to assess the level of erosion hazard in Kapanewon Panggang, and to formulate a land management concept based on actual land use conditions with erosion criticality parameters in Kapanewon Panggang, Gunungkidul Regency, Special Region of Yogyakarta. The method used is the USLE (Universal Soil Loss Equation). USLE is an erosion model designed to predict long-term erosion from sheet or rill erosion under specific conditions. USLE is used on both agricultural and non-agricultural lands. The results show that the erosion hazard levels in Kapanewon Panggang are categorized as very light (1184.28 hectares), light (1074.65 hectares), moderate (1831.70 hectares), severe (2411.01 hectares), and very severe (2628.38 hectares). The factors that most influence the magnitude of erosion are land use, slope length, and steepness. The land management concept to minimize erosion can be implemented based on land cover, namely in residential areas where water infiltration areas are needed, in savanna land use where additional vegetation and ground cover plants are necessary, and based on slope length and steepness, mechanical conservation by constructing bench terraces and stone bunds should be applied.